2018
DOI: 10.1038/s41467-018-07122-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype loss is associated with widespread divergence of the gene regulatory landscape in evolution

Abstract: Detecting the genomic changes underlying phenotypic changes between species is a main goal of evolutionary biology and genomics. Evolutionary theory predicts that changes in cis-regulatory elements are important for morphological changes. We combined genome sequencing, functional genomics and genome-wide comparative analyses to investigate regulatory elements in lineages that lost morphological traits. We first show that limb loss in snakes is associated with widespread divergence of limb regulatory elements. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 75 publications
4
75
0
Order By: Relevance
“…Similarly, our study showed that perturbing a single lens repressor element in a model organism, where the entire genetic machinery required for functional eyes is intact, did not result in a detectable organismal phenotype. However, we have previously shown that numerous components of the genetic "eye-making" machinery are highly diverged in the BMR and other subterranean mammals, as these species lost several eye-related genes and exhibit divergence in hundreds of eye regulatory elements (21)(22)(23). This suggests that eye degeneration in subterranean mammals most likely has a polygenic basis and that perturbations of several regulatory elements are necessary to obtain a detectable phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, our study showed that perturbing a single lens repressor element in a model organism, where the entire genetic machinery required for functional eyes is intact, did not result in a detectable organismal phenotype. However, we have previously shown that numerous components of the genetic "eye-making" machinery are highly diverged in the BMR and other subterranean mammals, as these species lost several eye-related genes and exhibit divergence in hundreds of eye regulatory elements (21)(22)(23). This suggests that eye degeneration in subterranean mammals most likely has a polygenic basis and that perturbations of several regulatory elements are necessary to obtain a detectable phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we used two comparative genomics approaches to identify and associate sequence and transcription factor (TF) binding site divergence in CNEs to the vision-impaired phenotype of the subterranean blind mole rat, naked mole rat, cape golden mole, and star-nosed mole (21,22). Both screens detected significantly higher sequence and binding site divergence in subterranean mammals in a locus that comprises two CNEs located 97 bp from each other ( Figures 1A,B).…”
Section: Divergence In a Lens Regulatory Element Near Tdrd7mentioning
confidence: 99%
See 3 more Smart Citations